Project AccessIT, Digitalization in Museums and Europeana (European Digital Library Project) - Latif Özen; Halil Demirdelen (Türk Kütüphaneciliği, 2011)
This article emphasizes the importance of digitizing museum inventory records and establishing a data set in solving the problems of collection management in the museums of Turkey. Besides, the museum staff is encouraged to share the already existing digital content at the Europeana Digital Culture Portal by means of AccessIT project.